Cyber-security threats, actors, and dynamic mitigation - Kolokotronis, Nicholas; Shiaeles, Stavros (Boca Raton : CRC Press, 2021)
"This book provides both a technical and state-of-the-art perspective as well as a systematic overview of the recent advances in different facets of cyber-security. It covers the methodologies for modelling attack strategies used by threat actors targeting devices, systems, and networks such as smart homes, critical infrastructures, and industrial IoT. With a comprehensive review of the threat landscape, the book explores both common and sophisticated threats to systems and networks. Tools and methodologies are presented for precise modelling of attack strategies, which can be used both proactively in risk management and reactively in intrusion prevention and response systems. Several contemporary techniques are offered ranging from reconnaissance and penetration testing to malware detection, analysis, and mitigation. Advanced machine learning based approaches are also included in the area of anomaly-based detection, that are capable of detecting attacks relying on zero-day vulnerabilities and exploits. Academics, researchers, and professionals in cyber-security who want an in-depth look at the contemporary aspects of the field will find this book of interest. Those wanting a unique reference for various cyber-security threats and how they are detected, analyzed, and mitigated will reach for this book often"--
Cyber-attackers' profiling / Dimitris Kavallieros (University of the Peloponnese, Center for Security Studies, Georgios Germanos (Univeristy of the Peloponnese, Nicholas Kolokotronis (University of the Peloponnese)
OCLC-licensed vendor bibliographic record.
Keywords: Computer security; Computer crimes -- Prevention; LAW / Forensic Science; TECHNOLOGY / Manufacturing; COMPUTERS / Security / General